ClC-5 Downregulation Induces Osteosarcoma Cell Apoptosis by Promoting Bax and tBid Complex Formation - Peng, Fei; Cai, Weisong; Li, Jianping; Li, Haohuan (Frontiers in Oncology, 2021)
Osteosarcoma is the most common malignant bone tumor. Chloride (Cl−) channels-mediated Cl− movement plays an important role in regulating the functions of various cancer cells, but its role in osteosarcoma remains unclear. In this study, we found that ClC-5 was increased in osteosarcoma tissues compared with normal bone tissues. Patients with high ClC-5 expression showed poor overall survival relative to those patients with low ClC-5 expression. Higher ClC-5 expression and lower intracellular Cl− concentration ([Cl−]i) were observed in osteosarcoma cells compared with normal osteoblasts. Lowering [Cl−]i increased the viability of osteosarcoma cells, which was markedly blocked by ClC-5 downregulation. Knockdown of ClC-5 significantly induced osteosarcoma cell apoptosis and increased the release of cytochrome c from mitochondria to cytosol, concomitantly with cleavage of caspase-9, caspase-3, and PARP. The effect of ClC-5 downregulation on osteosarcoma cell apoptosis and viability was abolished by caspase-3 and caspase-9 inhibitors, but not caspase-8 inhibitor. Furthermore, ClC-5 inhibition promoted Bax translocation from cytosol to mitochondria. Immunoprecipitation showed that ClC-5 interacted with Bax and ClC-5 downregulation enhanced Bax and tBid complex formation. Collectively, we demonstrate that ClC-5 downregulation induces osteosarcoma cell apoptosis via mitochondria-dependent apoptotic pathway activation by promoting Bax and tBid association and subsequent Bax translocation.